Екстенсивні/неекстенсивні статистики для pT розподілів різних заряджених частинок, народжених у p + p та A + A зіткненнях у широкому діапазоні енергій - Yassin, H.; Tawfik, A.N.; Abo Elyazeed, E.R. (Publishing house "Academperiodika", 2022)
A comprehensive review on various experimental parametrizations proposed to fit the transverse momentum distributions of charged pions, kaons, and protons produced at energies ranging between 7.7 GeV and 2.76 TeV is introduced. We present a systematic study for their statistical fits to the extensive Maxwell–Boltzmann (MB) and nonextensive statistics (generic axiomatic statistics and the Tsallis one as a special case). The inconsistency that the MB approach is to be utilized in characterizing the chemical freezeout, while the Tsallis approach determining the kinetic freezeout is discussed. The resulting energy dependence of the different fit parameters largely varies with the particle species and the degree of (non)extensivity. This manifests itself in that the Tsallis nonextensive approach seems to work well for p + p, rather than for A + A collisions. Nevertheless, discussing the deeper physical insights of nonextensive statistical approaches is not targeted, drawing a complete picture of the utilization of the Tsallis statistics in modeling the transverse momentum distributions of several charged particles produced at a wide range of energies and, accordingly, presenting a criticism or a support of the relevant works. This may be considered as the main advantage of this review.